Do GWAS-Identified Risk Variants for Chronic Lymphocytic Leukemia Influence Overall Patient Survival and Disease Progression? - Cabrera-Serrano, Antonio José; Sánchez-Maldonado, José Manuel; Ter Horst, Rob; Macauda, Angelica; García-Martín, Paloma; Benavente, Yolanda; Landi, Stefano; Clay-Gilmour, Alyssa; Niazi, Yasmeen; Espinet, Blanca; Rodríguez-Sevilla, Juan José; Pérez, Eva María; et al. (International journal of molecular sciences, 2023)
Chronic lymphocytic leukemia (CLL) is the most common leukemia among adults worldwide. Although genome-wide association studies (GWAS) have uncovered the germline genetic component underlying CLL susceptibility, the potential use of GWAS-identified risk variants to predict disease progression and patient survival remains unexplored. Here, we evaluated whether 41 GWAS-identified risk variants for CLL could influence overall survival (OS) and disease progression, defined as time to first treatment (TTFT) in a cohort of 1039 CLL cases ascertained through the CRuCIAL consortium. Although this is the largest study assessing the effect of GWAS-identified susceptibility variants for CLL on OS, we only found a weak association of ten single nucleotide polymorphisms (SNPs) with OS (p < 0.05) that did not remain significant after correction for multiple testing. In line with these results, polygenic risk scores (PRSs) built with these SNPs in the CRuCIAL cohort showed a modest association with OS and a low capacity to predict patient survival, with an area under the receiver operating characteristic curve (AUROC) of 0.57. Similarly, seven SNPs were associated with TTFT (p < 0.05); however, these did not reach the multiple testing significance threshold, and the meta-analysis with previous published data did not confirm any of the associations. As expected, PRSs built with these SNPs showed reduced accuracy in prediction of disease progression (AUROC = 0.62). These results suggest that susceptibility variants for CLL do not impact overall survival and disease progression in CLL patients.
Keywords: overall survival; Genetic Predisposition to Disease; Risk Factors; chronic lymphocytic leukemia; progrese nemoci; TTFT; genetic variants; Adult; Genome-Wide Association Study; dospělí; jednonukleotidový polymorfismus; Disease Progression; polygenic risk score; susceptibility; Leukemia, Lymphocytic, Chronic, B-Cell; Polymorphism, Single Nucleotide; lidé; Humans; rizikové faktory; chronická lymfatická leukemie; genetická predispozice k nemoci; celogenomová asociační studie